2023
DOI: 10.1039/d2nr04530c
|View full text |Cite
|
Sign up to set email alerts
|

Centimetre-scale single crystal α-MoO3: oxygen assisted self-standing growth and low-energy consumption synaptic devices

Abstract: High-density storage and neuromorphic devices based on 2D materials are hindered by large-scale growth. Moreover, the lack of mature mechanism makes it difficult to obtain high-quality single crystals in large-scale...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The highly oxygen-deficient region near the WS 2 layer ensured the resistance switching behavior based on the SCLC effect and could mimic a series of synaptic functions, such as LTP/LTD and STDP. In addition, Shan et al reported a 2T synaptic device that consists of Au/2D α-MoO 3 /Ti (Figure g) . The working mechanism is shown in Figure h.…”
Section: Synaptic Devices Based On 2d Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The highly oxygen-deficient region near the WS 2 layer ensured the resistance switching behavior based on the SCLC effect and could mimic a series of synaptic functions, such as LTP/LTD and STDP. In addition, Shan et al reported a 2T synaptic device that consists of Au/2D α-MoO 3 /Ti (Figure g) . The working mechanism is shown in Figure h.…”
Section: Synaptic Devices Based On 2d Materialsmentioning
confidence: 99%
“…(i) The mimicked LTP/LTD based on Au/α-MoO 3 /Ti. Reproduced with permission from ref . Copyright 2022 Royal Society of Chemistry.…”
Section: Synaptic Devices Based On 2d Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, as previously reported, new layered oxide materials such as MoO 3 can potentially function as high-κ materials with a larger bandgap (>3 eV) and high electron affinity (>6 eV). , Considering the most common 2D insulator h-BN as an example, the fabrication of high-performance devices is based on the synthesis of highly pure h-BN single crystals using high-temperature and high-pressure methods . Despite the recent demonstration of MoO 3 as a dielectric material, the current approaches for synthesizing MoO 3 single crystals that rely on evaporation, chemical vapor deposition, and physical vapor deposition were limited by either the small crystal size or complex high-temperature vapor process. , Therefore, a method of producing high-quality MoO 3 by removing defects is needed to prospectively improve the dielectric performance of this material. Herein, instead of the commonly used physical vapor deposition method, we utilize the oxidation of molybdenum chloride to synthesize millimeter-sized MoO 3 single crystals that can be efficiently exfoliated into flakes as thin as a few nanometers and as large as hundreds of micrometers.…”
Section: Introductionmentioning
confidence: 99%
“…High-surface-area plasmonic MoO 3−x was synthesised [55]. Centimetre-scale single-crystal α-MoO 3 was obtained [56], which was used in synaptic devices. Lin and co-workers [57] studied the band structure tuning of α-MoO 3 via tin intercalation.…”
Section: Introductionmentioning
confidence: 99%